Evaluating the Performance of Rice Genotypes for Improving Yield and Adaptability Under Direct Seeded Aerobic Cultivation Conditions - Sandhu, Nitika; Yadaw, Ram Baran; Chaudhary, Bedanand; Prasai, Hari; Iftekharuddaula, Khandakar; Venkateshwarlu, Challa; Annamalai, Anandan; Xangsayasane, Phetmanyseng; Battan, Khushi Ram; Ram, Mangat; Cruz, Ma. Teresa Sta.; Pablico, Paquito; et al. (Frontiers in Plant Science, 2019)
With the changing climatic conditions and reducing labor-water availability, the potential contribution of aerobic rice varieties and cultivation system to develop a sustainable rice based agri-food system has never been more important than today. Keeping in mind the goal of identifying high-yielding aerobic rice varieties for wider adaptation, a set of aerobic rice breeding lines were developed and evaluated for grain yield, plant height and days to 50% flowering in 23 experiments conducted across different location in Philippines, India, Bangladesh, Nepal and Lao-PDR between 2014-2017 in both wet and dry seasons. The heritability for grain yield ranged from 0.52 to 0.90. The season-wise two-stage analysis indicated significant genotype x location interaction for yield under aerobic conditions in both wet and dry seasons. The genotype x season x location interaction for yield was non-significant in both seasons indicating that across seasons the genotypes at each location did not show variability in the grain yield performance. Mean grain yield of the studied genotypes across different locations/seasons ranged from 2085 to 6433 Kg ha-1. The best-fit model for yield stability with low AIC value (542.6) was AMMI(1) model. The identified stable genotypes; IR 92521-143-2-2-1, IR 97048-10-1-1-3, IR 91326-7-13-1-1, IR 91326-20-2-1-4 and IR 91328-43-6-2-1 may serve as novel breeding material for varietal development under aerobic system of rice cultivation. High yield and stable performance of promising breeding lines may be due to presence of the earlier identified QTLs including grain yield under drought, grain yield under aerobic conditions, nutrient uptake, anaerobic germination, adaptability under direct seeded conditions and tolerance to biotic stress resistance such as qDTY2.1, qDTY3.1, qDTY12.1, qNR5.1, AG9.1, qEVV9.1, qRHD1.1, qRHD5.1, qRHD8.1 qEMM1.1, qGY6.1, BPH3, BPH17, GM4, xa4, Xa21, Pita and Pita2. The frequency of xa4 gene was highest followed by qAG9.1, GM4, qDTY3.1, qDTY2.1, qGY6.1 and qDTY12.1.